2018
DOI: 10.1016/j.quascirev.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene relative sea levels near Palmer Station, northern Antarctic Peninsula, strongly controlled by late Holocene ice-mass changes

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 80 publications
3
18
0
Order By: Relevance
“…1), respectively. Simms et al (2018) find changes in sea level along the Antarctic Peninsula are likely recording recent ice-sheet loading history rather than GIA following the last deglaciation. In particular, a late-Holocene increase in the rate of sea-level fall could reflect recent ice retreat following a readvance after the last deglaciation, similar to observations to the south of the West Antarctic ice sheet (Bradley et al, 2015;Kingslake et al, 2018).…”
Section: Interglacial Relative Sea-level Changementioning
confidence: 81%
See 3 more Smart Citations
“…1), respectively. Simms et al (2018) find changes in sea level along the Antarctic Peninsula are likely recording recent ice-sheet loading history rather than GIA following the last deglaciation. In particular, a late-Holocene increase in the rate of sea-level fall could reflect recent ice retreat following a readvance after the last deglaciation, similar to observations to the south of the West Antarctic ice sheet (Bradley et al, 2015;Kingslake et al, 2018).…”
Section: Interglacial Relative Sea-level Changementioning
confidence: 81%
“…Their results highlight the complexity in isolating different drivers and thus estimating global mean sea-level change from local relative sea-level change (e.g., Kopp et al, 2016). Both Simms et al (2018) and Barnett et al (2018) show the difficulty in defining a baseline period in sea level against which current changes can be assessed and future predictions made.…”
Section: Interglacial Relative Sea-level Changementioning
confidence: 98%
See 2 more Smart Citations
“…Recently, several studies have demonstrated the potential of using large clasts in OSL dating (e.g. Simms et al 2011Simms et al , 2018Sohbati et al 2011Sohbati et al , 2015Simkins et al 2013). These studies relied on the exposure of the clast surface to daylight, and the resulting resetting of the latent luminescence to some depth into the clast interior.…”
mentioning
confidence: 99%